Oral bacteria in patients with acute leukemia linfocítica. - Torres Ramos, Gilmer (2006)
Nowadays, even the presence of a complex oral micro-flora, it is possible to cure Acute Linphoblastic Leucemic patients. Upon 200 different species have been isolated, the majority is transient, and just 20 are resident species. Our investigation analyzed 106 LLA patients treated in the Neoplasic Diseases Peruvian Institute (INEN) since January to December 2001, whit the aim to state the oral micro flora, emphasizing in the opportunistic species that may cause systemic pathologies. It consisted in a retrospective clinic histories review, the data included age, sex, laboratory tests such as Hemogrham and Mieloghram. The microbiologic analysis was performed at the beginning of the hospitalization before receiving chemotherapy. The samples were processed in the INEN microbiologic laboratories, using Blood Agar for the primary isolation of all microorganisms ; Azida Agar for Gram (+) coccus; Macconkey Agar for Enterobacteriaceae ; Salad Manitol Agar for Stafilococcus and Sabouroud Agar for yeast. There were identified pathogenic residents species and opportunistic. The most frequent were the first group. In leucopenia and neutropenia patients, the more frequently found microorganisms were alpha hemolytic Streptococcus in 77 patients and Moraxella spp in 11 patients.